The effects of trade facilitation on trade performance in Africa - Daniel Sakyi; Sylvanus Kwaku Afesorgbor (Journal of African Trade, 2019)
Institutional trade barriers constitute substantial constraints for a number of exporters and importers. These barriers are multidimensional and they impede trade flows and trade performance of many developing countries, including African countries. In particular, the International Trade Centre through its series of business surveys has identified that a myriad number of businesses within Africa are affected by these barriers. Notwithstanding, there is little empirical knowledge on how they interact and affect trade flows within Africa. In this paper, we assess the effects of trade facilitation measures and their combined effect (using principal component analysis) on trade performance in a sample of 52 African countries within a structural gravity model framework for the period 2006-2015. The results suggest that trade facilitation improves trade performance in Africa; the better the level of trade facilitation, the larger the extent of trade flows. From a policy perspective, reducing trade costs across borders remains key to improve trade performance in Africa.
Keywords: C23; F10; F43; O47; O55; 330; Africa; gravity model; trade facilitation; trade flows